Research impact of governance activities on business efficiency of real estate industry companies listed on the Vietnam stock exchange - Lê Na; Nguyễn Danh Thịnh; Trần Đình Lý (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2023)
The study aims to measure the influence of management activities on the business performance of the companies. The study conducted a random sampling of 180 financial statements, for 12 consecutive years, of 15 real estate companies listed on Vietnam’s stock exchange. Statistical results show that the board of directors of companies usually has from 03 to 05 members, and most of the directors are concurrently members of the board of directors. Companies with business results and efficiency have increased quite rapidly over the years. The analysis results of the Fixed Effect Model (FEM) and Random Effect Model (REM) show that there is a negative relationship between financial leverage variables; company size by assets, and the gender of the chief accountant with business performance. As for the debt/equity ratio variables; the coefficient of fixed assets; labor scale; The age of the company, and the proportion of women on the board of directors have a positive relationship with business performance.